Wireless sensor network based monitoring system for precision agriculture in Uzbekistan - Farruh Muzafarov; Abdimurod Eshmuradov (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
The last decades the WSN technology has been adopted by more and more scientific fields for accurate and effective monitoring of climate phenomena like air pollution, destruction phenomena like landslides, etc. It has been widely used in agriculture for field monitoring. WSN is an emerging technology, which through the research in the labs and the real deployments has been proved to be a significant and valuable tool for scientists to explore another world which is behind the various environmental phenomena using tiny sensor nodes In this article, "Expert Advisory System" was developed to improve the productivity of farmers, save their time and improve the efficiency of the crops. The system monitors real-time crop fields using wireless sensor networks and provides the necessary information to farmers via the Internet. The farmer will be required to undertake the necessary remedial action on the basis of the information received. It’s also provided that the simulation of WSN in Contiki Simulator tool. Moreover, the queing model for WSN to also considered in this work.